2022
DOI: 10.3390/microorganisms10071279
|View full text |Cite
|
Sign up to set email alerts
|

Human Breast Milk: A Source of Potential Probiotic Candidates

Abstract: This study focuses on the isolation of lactobacilli/bifidobacteria from human breast milk and their first characterization, in the perspective to find new probiotic candidates to be included in food products. More specifically, breast-milk-isolated strains demonstrated a very good aptitude to adhere to intestinal cells, in comparison with L. rhamnosus GG strain, taken as reference. The same behavior has been found for hydrophobicity/auto-aggregation properties. A remarkable antagonistic activity was detected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The breast milk samples were treated to remove fat and 1 mL of the samples was centrifuged at 7150 g for 20 minutes [10]. Then total DNA was isolated from the pellets using GENEJET GENOMIC DNA PURIFICATION KIT® (Thermo Scientific).…”
Section: Dna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The breast milk samples were treated to remove fat and 1 mL of the samples was centrifuged at 7150 g for 20 minutes [10]. Then total DNA was isolated from the pellets using GENEJET GENOMIC DNA PURIFICATION KIT® (Thermo Scientific).…”
Section: Dna Extractionmentioning
confidence: 99%
“…Studies have shown that Bifidobacterium and Lactobacillus are among the recurring bacteria [10] [11]. The presence of Bifidobacterium and Lactobacillus is stable over time among individuals but varies widely within populations and between countries [12].…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli SO107 and Streptococcus agalactiae SO104 were isolated at Sant'Orsola-Malpighi University Hospital of Bologna (Italy) during routine diagnostic procedures [18,19]. Enterotoxigenic E. coli (ETEC), Salmonella enterica, Yersinia enterocolitica, and Enterococcus faecium BC105 belong to the Department of Pharmacy and Biotechnology of University of Bologna [19,20]. These strains were aerobically grown at 37 • C in Brain Heart Infusion (BHI, Difco).…”
Section: Microorganisms and Culture Conditionsmentioning
confidence: 99%